2010
DOI: 10.1007/s11538-010-9553-0
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Treatment Interruptions During Imatinib Treatment of Chronic Myelogenous Leukemia

Abstract: Although imatinib is an effective treatment for chronic myelogenous leukemia (CML), and nearly all patients treated with imatinib attain some form of remission, imatinib does not completely eliminate leukemia. Moreover, if the imatinib treatment is stopped, most patients eventually relapse (Cortes et al. in Clin. Cancer Res. 11:3425–3432, 2005). In Kim et al. (PLoS Comput. Biol. 4(6):e1000095, 2008), the authors presented a mathematical model for the dynamics of CML under imatinib treatment that incorporates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 21 publications
(64 reference statements)
2
21
0
Order By: Relevance
“…14 Many additional models have been suggested in the last decade. Recent articles include work by Michor and coworkers, 15,16 Dingli and coworkers, 17 Roeder and coworkers, 18 Levy and coworkers, 19,20 and many others (reviewed in Whichard et al 9 and Roeder and d'Inverno, 21 and in supplemental Section 1, available on the Blood Web site; see the Supplemental Materials link at the top of the online article). Importantly, such models can generate useful new insights by quantitatively interrelating datasets that seem offhand to have little connection with each other, let alone to have systematic numerical correlations.…”
Section: Cell Population Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Many additional models have been suggested in the last decade. Recent articles include work by Michor and coworkers, 15,16 Dingli and coworkers, 17 Roeder and coworkers, 18 Levy and coworkers, 19,20 and many others (reviewed in Whichard et al 9 and Roeder and d'Inverno, 21 and in supplemental Section 1, available on the Blood Web site; see the Supplemental Materials link at the top of the online article). Importantly, such models can generate useful new insights by quantitatively interrelating datasets that seem offhand to have little connection with each other, let alone to have systematic numerical correlations.…”
Section: Cell Population Dynamicsmentioning
confidence: 99%
“…Latency times do, however, enter, directly or indirectly, into many clinically relevant predictions, 12 especially for the possibility of relapse after discontinuation or interruption of kinase inhibitor treatment subsequent to complete molecular remission. 20 Most quantitative CML models imply that, if T has a large mean and/or SD, relapses can still occur long after the treatment has stopped. And some models further predict that a large latency time SD is associated with a higher probability of developing TKI resistance (reviewed in Katouli and Komarova 68 ; the mathematical rationale for this association is outlined in supplemental Section 1.4).…”
Section: Importance For CML Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [12], Paquin et al used the delay differential equations model presented in [6] to study the effectiveness of strategic treatment interruptions as a potential clinical approach to enhancing the effects of imatinib treatment for CML. The authors demonstrated that treatment programs that involve strategic treatment interruptions in which imatinib treatment is temporarily stopped in order to leverage the antileukemia immune response may prevent leukemia from relapsing and may prevent remission for significantly longer than continuous imatinib treatment, and, in many cases, strategic treatment interruptions may completely eliminate leukemic cells from the body.…”
Section: Introductionmentioning
confidence: 99%
“…Several models for the description of the origin and evolution of CML on a cellular level have been proposed, see for example, and the literature therein. In more general terms, models for the proliferation of metastases are given in , and, with respect to the signaling between cells, which is considered a crucial part when it comes to understanding tumors, in .…”
Section: Introductionmentioning
confidence: 99%